La hipnosis y la subjetividad: Reflexiones sobre la ciencia moderna y Psicología (2009)
The present article calls for a critical and epistemological reconsideration of hypnosis and its relation with the science of modern psychology. In that sense, it searches for a two-way discussion, which brings up various contradictions present in the upbringing of such science in modern aspects. First of all, this article highlights the difficulties in putting together clinic and science; in addition, it suggests that the views over hypnosis might as well be applicable, in a general approach, to clinic psychology, which in turn supposes that those thoughts brought by hypnosis are still of considerable pertinence to such association - clinic and science. Second, this article also states that the institutions involved in the formation of psychology did have a crucial role in determining a distorted view not only over hypnosis but also of what could or could not be considered scientific. The present article finally proposes that, although the study of hypnosis does not show a whole array of answers in the modern sense, it still is rather pertinent when it comes to bringing important questions concerning the building of such a science. Some of these questions relate to historical deformations brought about by institutional processes and the scientific aspect of clinic practice.